Quality of lfe in families of children with developmental disabilities: The impact of family characteristics and stress levels - Perućica Ranka R.; Kalajdžić Olivera B.; Bakoč Andrijana B.; Živanović Sanja M.; Škipina Daliborka B. (Zbornik Radova Filozofskog Fakulteta u Prištini)
The quality of life in families of children with developmental disabilities significantly influences family functionality and the well-being of all members. Various family characteristics often affect this quality. This study aimed to examine the impact of family characteristics and family stress levels on the quality of life in families of children with developmental disabilities. The sample consisted of 122 parents of children with developmental disabilities. Data were collected using a sociodemographic questionnaire, the Beach Center Family Quality of Life Scale (Beach FQOL Scale), and the Stress Symptoms Scale-16. The results showed that parents rated their family's quality of life as satisfactory, with Family Interactions being the highest-rated domain and Emotional Well-being the lowest. Families with only one child reported better quality of life in the domains of Family Interactions, Parenting, and Support compared to families with three or more children. Families of children with hearing, speech, or voice impairments reported the highest satisfaction in the Family Interactions domain. Furthermore, the findings indicated that parents in the sample experienced relatively low stress levels, with no significant correlation between family quality of life and stress levels.